Baseline LDL-C and Lp(a) Elevations Portend a High Risk of Coronary Revascularization in Patients after Stent Placement - Cai, Anping; Li, Liwen; Zhang, Ying; Mo, Yujin; Li, Zhigen; Mai, Weiyi; Zhou, Yingling (Disease Markers, 2013)
Background and Aim. Incidence of coronary restenosis after stent placement is high. Our study was going to investigate whether Lp(a) elevation was potential for predicting coronary restenosis and whether the effects of Lp(a) elevation on coronary restenosis were dependent on LDL-C level. Methods and Results. Totally 832 participants eligible for stent placement were enrolled and followed up for monitoring clinical end points. Baseline characteristics were collected. According to the cut point of Lp(a), participants were divided into low Lp(a) group (Lp(a) < 30 mg/dL) and high Lp(a) group (Lp(a) ≥ 30 mg/dL). Furthermore, based on baseline LDL-C level, participants were divided into LDL-C < 1.8 mmol/L and ≥1.8 mmol/L subgroups. Clinical end points including major adverse cardiovascular events (MACE), cardiovascular death, nonfatal myocardial infarction, ischemic stroke, and coronary revascularization (CR) were compared. Patients in high Lp(a) groups more frequently presented with acute coronary syndrome and three vessel stenoses. In subgroup of LDL-C < 1.8 mmol/L, no significant differences of cardiovascular outcomes were found between low and high Lp(a) groups. While in the subgroup of LDL-C ≥ 1.8 mmol/L, incidences of MACE and CR were significantly higher in high Lp(a) group, and odds ratio for CR was 2.05. Conclusion. With baseline LDL-C and Lp(a) elevations, incidence of CR is significantly increased after stent placement.